In vitro evaluation of the Antimicrobial Activity of four resin based Endodontic Sealers on three bacterial species (Mustansiria Dental Journal, 2018)
Aim: The aim of this in vitro study was to evaluate the antimicrobial action of fourresin based endodontic sealers after 24 hrs.Materials and Method: The freshly mixed sealers were AH26, AH-plus, Epiphanyand Topseal. They were prepared according to manufacturer’s instruction andplaced in prepared wells of 40 agar plates inoculated with Streptococcus viridans,Staphylococcus aureus and Enterococcus faecalis. (10 samples for eachmicroorganism). Four cavities, each one measuring 5 ml in diameter and 4 ml indepth, were made in each agar plate using cork poorer. Agar diffusion method onMuller Hinton agar was employed, and zones of inhibition were measured after1day.Results: AH26 containing proved to be the most effective against all microorganismstested. This was followed by Epiphany. Topseal which showed antibacterialactivity on all tested microorganisms slightly higher than that of AH-Plus whichshowed the least action on all tested microorganisms.Conclusion: All the sealers evaluated in this study showed different inhibitory effectagainst all bacterial strains.